Internationale Bildungskooperation im Bereich Deutsch als Fremdsprache (Brill, 2025)
Collaboration research is a multidisciplinary and international research area, the complexity of which is also reflected in the multitude and diversity of face-to-face, digital and hybrid exchange formats. This includes, among other things, student exchanges, student mobility, exploration projects, teaching and research collaborations and various formats of internationalization at home. This volume provides an inventory of research into international educational collaborations and mobilities in the field of DaF (German as a Foreign Language) and addresses research subjects such as the design of interactions and the acquisition of communicative and cultural awareness skills, the reflected use of media and methods in exchange encounters, as well as cultural, language and educational policy discussions. Interdisciplinary issues such as the interaction of language and subject learning in interdisciplinary educational projects and the professionalization of teachers are also discussed.